Evaluation of guidelines for chemical stabilization of tropical residual soils / Asmidar Alias, Bujang B.K. Huat and Azlan Abdul Aziz - Alias, Asmidar; Huat, Bujang B.K.; Abdul Aziz, Azlan (2006)
Soil stabilization has been widely used based on the effectiveness and as an alternative to substitute the lacking of suitable material on site. Past research works on stabilizing residual soil have shown various results depending on the selection and application of various additives, Guidelines and standards have been developed to assist practitioners in designing road structure by means of chemical stabilization. TRL (1993), US Army (1994), and PWD (1985) are some of the authorities that endeavor with either extensive or acceptable guide for the process. However, precedent research' works shows deficiency in applying these guidelines. Efforts were made in this paper to review these guidelines for chemical stabilization of residual soil. TRL (1993) was found to give a more simplified route in the selection of suitable binders for the soil stabilization process. TRL could also be readily adaptable to the practice in the country as the standards used (i,e. the British Standards) are commonly used for the testing of local soils.